Studies on flow properties of Bengal gram (Cicer arietinum) flour for effective handling and storage strategies. (29th September 2021) - Handu, Sheetal; Upadhyay, Ashutosh; Jan, Shumaila
Abstract: Bengal gram flour is in great demand and has extensive application due to its nutritional, functional, and sensory properties. The study summarizes the characteristics and compared the flow behavior of two varieties of Bengal gram flour (P372 and P3043) with commercial Barik sample with respect to chemical composition, wettability, physical properties, shear properties, compressibility, and dynamic properties, along with particle size and shape. The result showed that the median particle size distribution of the Bengal gram flour samples ranged between 53.59 and 63.46 μm. More fine particles were found in commercial Barik sample (11.09 μm), and larger particles were found in P372 (118.07 μm) and P3043 (116.47 μm). Similarly, the particle shape (circularity) was found higher in P372 (0.84) and P3043 (0.73) as compared to the commercial Barik sample (0.65). The chemical composition of mainly fat (%) and protein (%) was higher and lower in commercial Barik sample, respectively, compared to P372 and P3043 Bengal gram flour. Wettability (contact angle) determined the solid–liquid interaction of Bengal gram flour, where the commercial Barik sample showed a higher contact angle compared to P372 and P3043. The flow properties of Bengal gram flour, that is, compressibility, shear, and dynamic measurements were analyzed using an FT4 powder rheometer. The results indicated better flow behavior of the two varieties P372 and P3043 compared to commercial Barik sample. Practical Applications: The flow properties of Bengal gram flour are essential during the handling, processing, transportation, mixing, compression, and packaging. The consistent flow of flour without excessive dust generation and spillage during handling is of great concern in the food industry. The flow properties of flour characterize its behavior during handling, conveying and storage. It is crucial for the design of storage and conveying systems such as hopper and silos in order to maximize the use of discharge units to their design capacity to prevent expensive downstream handling problems. The practical application obtained from the comparative study would be useful to determine the effect of various environmental conditions on the flowability of Bengal gram flour. Thus, it provides critical factors in optimizing the processing, designing of equipment, hoppers, and silos used to produce Bengal gram flour in the food industry. Abstract : The graphical abstract represents categories of powder i.e. cohesive and non‐cohesive powders. The reasons that cause various forms of flow difficulties are mentioned below. The flow parameters of two varieties of Bengal gram flour (P372 and P3043) are compared to commercial flour in this research paper. The graphical abstract also show the equipment used to conduct the study.